The Vosges, border of Alsace (1871-1914) - Sébastien Stumpp; Julien Fuchs (Revue de Géographie Alpine)
During the annexation of Alsace by Germany between 1871 and 1914, the Vosges mountain range took on particular significance for the inhabitants of the region. It represented a boundary that both allowed the Alsatian people to assert their cultural distinctiveness, while at the same time ‘integrating’ Alsace into France, thereby symbolically preserving the region from attempts to assimilate it into the Reich. The way in which local mountain associations promoting hiking and skiing considered this political and cultural border reveals their unique perception of a natural boundary that was fixed by definition, but mobile in its representations. As we will see, these associations tended to particularly promote the existence of a cultural border area – real and imagined – that effectively set the Alsace region apart from both France and Germany. Within this context, the images of the ‘blue line of the Vosges’ held by the Alsatian members of these clubs differed greatly. Some considered it to be a unifying border that perpetuated the myth of the lost provinces, ritualised the crossing of the Franco-German border, and symbolised their strong ties with the French Alpine Club. Others saw the Vosges more as a dividing border, placing emphasis on language specificities and differences in cultural heritage, the use of mountain huts as centres to celebrate local traditions, and the integration of the mountain range within the ‘regional heritage’. In this sense, the main issue here was not so much the mobility of the political borders (from the Rhine to the Vosges during the German annexation of Alsace), but rather the shifts in the very meaning attributed to this border area.